Institute Document Automization System - Shinde Sandip; Jape Prajakta; Shinde Prajakta; Nagapalle Pritee; Prof. Bhise A.K (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper presents the achievements of an experimental project called Maurdor (Moyens AUtomatisés de Reconnaissance de Documents ecRits – Automatic Processing of Digital Documents) funded by the French DGA that aims at improving processing technologies for handwritten and typewritten documents in French, English and Arabic. The first part describes the context and objectives of the project. The second part deals with the challenge of creating a realistic corpus of 10,000 annotated documents to support the efficient development and evaluation of processing modules. The third part presents the organisation, metric definition and results of the Maurdor International evaluation campaign. The last part presents the Maurdor demonstrator with a functional and technical perspective.